Pemanfaatan Limbah Organik Rumah Tangga Sebagai Sumber Bahan Baku Pupuk Cair Di Desa Denggen Timur, Kecamatan Selong, Kabupaten Lombok Timur - Firiyan Saputra; Putri Adhelia Pratiwi; Rica Salwani; Mariyanah; Jumadep; Yuyu Ilma Shahwaningsih; Nazila Aulia; Ni Ketut Anggreni; Widia Sari; Ade Rahman (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The management of household organic waste in rural areas remains an environmental problem, including in Denggen Timur Village, Selong District, East Lombok Regency, where most waste is still disposed of without being processed. However, organic waste has great potential to be reused as valuable products, one of which is liquid organic fertilizer (POC). This activity aims to increase community knowledge and skills in processing household organic waste into POC as an alternative to environmentally friendly fertilizers. The methods used include a preparation stage through field surveys, an implementation stage in the form of socialization and direct practice of POC production, and an evaluation and reporting stage. The activity was carried out with the involvement of the Sopok Kena Farmers Group Association (Gapoktan), the village government, and resource persons from the West Nusa Tenggara. Province Environment and Forestry Service. The results of the activity showed an increase in the community's understanding and enthusiasm for organic waste management, as well as the participants' ability to independently produce liquid organic fertilizer. The POC product that was produced has undergone a fermentation process and was distributed to the community to be applied directly to plants. This activity contributed to reducing organic waste, increasing environmental awareness, and supporting community-based sustainable agriculture in Denggen Timur Village.